MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA ASPEK MENULIS MELALUI METODE PEMBELAJARAN INKUIRI - Sidiq (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This study aims to find out the implementation of learning implementation learning by using inquiry method as well as improving learning achievement of Indonesian language aspects of writing grade 6 students of SD Negeri Wudi, Sambeng Sub-district, Lamongan District, academic year 2016/2017. The subject of this research is all students of class VI SD Negeri Wudi which amounted to 8 people. This study belongs to a classroom action research consisting of several cycles with each cycle consisting of planning, action, observation, and reflection. Instruments used in the form of Learning Plans (RP), Student Activity Sheets (LKS), and grade assessment. The results showed an increase in student learning outcomes. In the first cycle there are 5 students who experience complete learning of individuals from 8 students (62.50%) this shows in this cycle has not experienced classical completeness. In cycle II there are 8 students who experience complete learning of individuals from 8 students (100%) this shows in this cycle has undergone classical mastery. And the increase of the average score of students is 61.25 in cycle I to 79.38 in cycle II.